Flexible ammonia gas sensor based on multi-heterojunction nanocluster as well as preparation method and application of flexible ammonia gas sensor
By preparing a multi-heterojunction MoO3/CuO/Cu2O mixed nanocluster layer on a PET substrate and covering the PTFE hydrophobic layer, the problem of detection of low-concentration ammonia at room temperature and signal distortion in high-humidity environments in the prior art is solved. A high sensitivity and stability of ammonia gas sensing effect is achieved.
Patent Information
- Application Number
- CN202411678786.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to detect ammonia in the low concentrations of expiratory gas at high sensitivity at room temperature, and there are problems of signal distortion and performance degradation in high humidity environments.
A multi-heterojunction MoO3/CuO/Cu2O hybrid nanocluster layer was used to prepare sensors on PET substrates by cluster beam deposition technology, and the PTFE hydrophobic layer was covered on the surface to improve moisture resistance.
High sensitivity detection of ammonia at room temperature is achieved, the selectivity and stability of the sensor are improved, and ammonia at the order of sub-ppm can be reliably detected in high humidity environments.
Smart Images

Figure CN119510518A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a gas sensing device, and in particular to a flexible ammonia gas sensor based on multi-heterojunction nanoclusters, and a preparation method and application thereof. Background Art
[0002] Ammonia (NH3) is a key biomarker, and its elevated concentration often indicates health problems such as kidney disease. In particular, detecting low concentrations of NH3 in exhaled breath is very important for non-invasive diagnosis. However, accurate detection of low concentrations of NH3 in exhaled breath remains a challenge due to the limitations of existing sensing technologies. Developing flexible NH3 sensors with high sensitivity, selectivity, and the ability to operate at room temperature is essential to achieve non-invasive medical diagnosis.
[0003] Conventional n-type metal oxide semiconductor (MOS) gas sensors such as SnO2, ZnO and TiO2 usually require high operating temperatures to show sufficient sensitivity, which limits their application in wearable and portable sensing devices. High operating temperatures increase power consumption, shorten the service life of flexible polymer substrates (such as PET), and may also pose safety risks. Therefore, it is particularly important to develop gas sensors that work at room temperature.
[0004] To overcome these limitations, p-type MOS materials, especially copper oxides (CuO and Cu2O), have been explored because of their ability to operate efficiently at room temperature. Copper oxides are attractive for gas sensing applications due to their narrow band gap, high oxygen adsorption capacity, and low cost. However, their gas sensing performance, including sensitivity and selectivity, still needs to be significantly improved to meet the practical application requirements of detecting sub-ppm levels of NH3 in breath analysis.
[0005] For non-invasive kidney disease diagnosis, NH3 detection requires high-performance gas sensing materials capable of detecting sub-ppm NH3 concentrations. The NH3 concentration in the breath of healthy individuals is approximately 0.8 to 0.9 ppm, while it can exceed 1.5 ppm in patients with uremia (DOI: 10.1038 / ki.1997.324). Therefore, it is crucial to develop sensors with enhanced sensitivity at room temperature, and the existing copper oxide performance is not sufficient to meet such demanding application requirements.
[0006] In addition, exhaled breath is a complex mixture containing thousands of gases, and the humidity is usually over 90% relative humidity. In exhaled breath analysis, accurately distinguishing NH3 from other gaseous species and effectively eliminating humidity interference pose key challenges to gas sensors. These challenges have prompted us to develop new sensing materials with high selectivity and moisture resistance. Despite certain progress in nanostructured sensing materials, including high surface area nanostructures and precious metal doping, condensation in humid environments remains a persistent challenge for exhaled breath gas sensors. Condensation causes signal distortion, performance degradation, and impaired sensor stability and reliability, emphasizing the need for innovative solutions.
[0007] Heterojunction engineering is considered a promising strategy to improve the sensing performance of MOS materials. By forming a heterojunction between different semiconductors, the charge transfer at the interface can be improved, thereby promoting surface reactions with target gases. In particular, multi-heterojunction structures can provide a synergistic effect and significantly enhance gas sensing performance.
[0008] In this paper, we introduced multi-heterojunction MoO3 / CuO / Cu2O hybrid nanoclusters to achieve excellent NH3 sensing performance at room temperature. The combination of MoO3 (n-type semiconductor) with CuO and Cu2O (p-type semiconductor) forms pn and pp heterojunctions, which are very beneficial for improving gas sensing properties. The formation of these heterojunctions enables efficient charge separation and improved adsorption of NH3 molecules, thus solving the above challenges and improving sensitivity, selectivity and stability.
[0009] The preparation of MoO3 / CuO / Cu2O was achieved by cluster beam deposition (CBD) technique, which allows precise control of copper oxidation state and multi-heterojunction formation. Unlike conventional wet chemical methods, which are often limited by reaction conditions and interface quality, the physical vapor deposition process based on reactive sputtering overcomes these limitations. It provides great flexibility in the preparation of HNC-assembled nanostructured films, making the preparation of MoO3 / CuO / Cu2O possible. In addition, by precisely adjusting the oxygen content in the aggregate growth chamber, this method achieves precise control of the composition of metal oxide nanoclusters. In addition, the sensor was coated with polytetrafluoroethylene (PTFE) by radio frequency sputtering to provide a hydrophobic layer, thereby improving stability in high humidity environments, which is an important feature for practical applications in breath analysis. Summary of the invention
[0010] In view of the above-mentioned technical problems existing in the prior art, the purpose of this application is to provide a flexible ammonia gas sensor based on multi-heterojunction nanoclusters, and its preparation method and application. The flexible NH3 gas sensor of this application is composed of MoO3 / CuO / Cu2O mixed nanoclusters prepared on a PET substrate by a dual-target cluster beam deposition method. The sensor utilizes the multi-heterojunction structure formed by MoO3, CuO and Cu2O to significantly improve the adsorption performance of NH3, and increases the active sites and surface energy, thereby improving the sensitivity and shortening the response time. The PTFE layer coated on the surface of the sensor can significantly reduce humidity interference, so that it maintains excellent performance in a high humidity environment. The sensor of the present invention can be used as a wearable sensor in environmental monitoring, medical diagnosis and food safety.
[0011] The technical solution adopted by the present invention is as follows:
[0012] A flexible NH3 gas sensor includes a PET (polyethylene terephthalate) substrate, a forked electrode, a MoO3 / CuO / Cu2O mixed nanocluster layer and a PTFE (polytetrafluoroethylene) hydrophobic layer, wherein the forked electrode is arranged on one side surface of the substrate, and a MoO3 / CuO / Cu2O mixed nanocluster layer is first deposited on the forked electrode on one side surface of the substrate, and MoO3 enhances the adsorption of NH3 by forming a multi-heterojunction with CuO and Cu2O, and then a PTFE hydrophobic layer is coated on the surface. The present invention reflects the external ammonia concentration by measuring the resistance change of the sensor. The MoO3 / CuO / Cu2O mixed nanocluster layer is used to enhance the adsorption capacity of NH3, the forked electrode is used to detect the change of resistance, and the PTFE hydrophobic layer is used to improve the stability of the sensor in a high humidity environment.
[0013] Furthermore, MoO3 / CuO / Cu2O mixed nanoclusters were deposited on a PET substrate by dual-target cluster beam deposition to form a multi-heterojunction structure; the sensor surface was coated with a PTFE hydrophobic layer (PTFE molecular weight was 300,000-600,000) to enhance moisture resistance and environmental adaptability.
[0014] Preferably, PET with a thickness of 50 to 1000 μm is selected as the device substrate (PET molecular weight is between 5000 and 25000), which has high mechanical flexibility and good chemical stability and can effectively support the MoO3 / CuO / Cu2O multi-heterojunction layer of the sensor.
[0015] Preferably, the MoO3 / CuO / Cu2O mixed nanocluster layer is prepared by a dual-target cluster beam deposition method, the MoO3 content is controlled at 3-7%, and the CuO / Cu2O nanocluster layer thickness is controlled at 10-500nm to ensure efficient NH3 adsorption and charge transfer performance.
[0016] Preferably, the interdigitated electrodes are made of titanium and silver and deposited on a PET substrate by electron beam evaporation technology, with an electrode spacing of 50 to 400 μm, which can improve the detection sensitivity and stability of resistance changes.
[0017] Preferably, the polytetrafluoroethylene (PTFE) hydrophobic layer is deposited by radio frequency magnetron sputtering technology, and the thickness is controlled at 500-5000 nm to reduce the interference of moisture on the sensor performance, thereby ensuring the reliability of the sensor in a high humidity environment.
[0018] The present invention also discloses a method for preparing the flexible ammonia gas sensor based on multi-heterojunction nanoclusters, comprising the following steps:
[0019] 1) preparing interdigital electrodes on a substrate by mask evaporation to obtain a substrate with interdigital electrodes;
[0020] 2) CuO / Cu2O nanoclusters are deposited on a substrate with interdigital electrodes by cluster beam deposition technology, metal Cu and Mo targets are placed on two sputtering guns of a cluster beam deposition device, the interdigital electrodes are placed in a deposition chamber of the cluster beam deposition system, and the entire device is evacuated; first, a sputtering gas is introduced into a sputtering gun loaded with a Cu target, and a buffer gas is introduced into the sputtering chamber of the cluster beam deposition system, wherein the buffer gas is mainly Ar and a small amount of O2 is introduced into the buffer gas, and incomplete oxidation of Cu is achieved by adjusting the oxygen content, thereby generating a heterogeneous structure of CuO / Cu2O mixed nanoclusters deposited on the interdigital electrodes on the surface of the substrate;
[0021] 3) After step 2), the O2 content in the buffer gas is increased, and another sputtering gun loaded with a Mo target sputters Mo in a reaction atmosphere containing a relatively high O2 content, thereby generating fully oxidized MoO3 and depositing it on the CuO / Cu2O mixed nanoclusters, thereby forming a multi-heterojunction structure of a MoO3 / CuO / Cu2O mixed nanocluster layer;
[0022] 4) A hydrophobic layer was coated on the surface of the MoO3 / CuO / Cu2O mixed nanocluster layer of the sensor using radio frequency magnetron sputtering to improve moisture resistance.
[0023] Further, in step 2), the pressure in the sputtering chamber is maintained at 100-150 Pa, the sputtering power of the Cu target is set to 10-15 W, the O2 content in the buffer gas is 0.01-0.02%, and the deposition rate is The deposition time is 100-2000 s, preferably 1200-2000 s.
[0024] Further, in step 3), the pressure in the sputtering chamber is maintained at 100-150 Pa, the sputtering power of the Mo target is set to 18-25 W, the O2 content in the buffer gas is 0.04-0.1%, and the deposition rate is The deposition time is 60-300s, preferably 100-300s. When depositing MoO3, the oxygen flow rate is adjusted to ensure that the Mo element is completely oxidized to Mo 6+ , thereby forming MoO3 with high adsorption activity and stability, and finally realizing MoO3 / CuO / Cu2O multi-heterogeneous structure.
[0025] The sensor of the present invention can be well applied to detecting ammonia concentration, can work in a temperature range of -10 to 60° C., and can maintain sensitivity and stability in an environment with a relative humidity of more than 90%.
[0026] The innovation of the present invention is that by introducing a MoO3 / CuO / Cu2O multi-heterojunction nanocluster layer, high-sensitivity detection of ammonia is achieved at room temperature; at the same time, the surface is covered with a PTFE layer, so that the device has good moisture resistance; combined with a PET substrate, the sensor has excellent mechanical flexibility and is suitable for wearable devices. By combining magnetron sputtering and cluster beam deposition, the manufacturing process is simplified and the production cost is reduced. The sensor of the present invention has good sensitivity, selectivity, response speed and mechanical stability, can reliably detect low concentrations of ammonia in a high humidity environment, and is suitable for food safety, human health monitoring and environmental gas monitoring and other fields.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1) The present invention utilizes the MoO3 / CuO / Cu2O multi-heterojunction structure to significantly improve the adsorption capacity of NH3 and the sensitivity of the sensor, and can efficiently detect ammonia at room temperature.
[0029] 2) The present invention combines a PET flexible substrate so that the sensor has good mechanical flexibility and environmental adaptability, and is suitable for wearable and portable devices.
[0030] 3) The present invention adopts radio frequency magnetron sputtering and cluster beam deposition technology, which simplifies the manufacturing process, reduces the cost, and ensures the high performance and consistency of the sensor.
[0031] 4) The sensor of the present invention has good moisture resistance and stability in a high humidity environment, and can reliably detect ammonia concentrations as low as sub-ppm in a high humidity environment. It can reliably detect ammonia and is suitable for application scenarios such as food safety monitoring, human health monitoring, and environmental gas monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic structural diagram of the flexible ammonia gas sensor of the present invention with multiple heterojunction nanoclusters;
[0033] Figure 2 A schematic diagram of a device for preparing a sensor according to the present invention;
[0034] Figure 3 The ammonia sensing response curves of CuO / Cu2O and MoO3 / CuO / Cu2O prepared in the present invention, the concentration of ammonia is marked above the curve, the unit is ppm;
[0035] Figure 4 The sensor response of the sensor covered with a PTFE hydrophobic layer and the sensor not covered with PTFE prepared in Example 2 of the present invention to ammonia under a series of humidity conditions; the left figure shows the real-time response curve, and the right figure shows the change of the sensor response value with humidity.
[0036] In the figure: 1-PET substrate, 2-MoO3 / CuO / Cu2O mixed nanoclusters, 3-interdigitated electrodes, 4-PTFE hydrophobic layer, 5-cluster beam deposition device, 6-RF magnetron sputtering gun, 7-sample stage. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0038] like Figure 1 As shown, the present invention relates to a flexible ammonia gas sensor, which comprises: a polyethylene terephthalate (PET) substrate 1, a MoO3 / CuO / Cu2O mixed nanoclusters 2, an interdigital electrode 3 and a PTFE hydrophobic layer 4. The interdigital electrode 3 is arranged on one side surface of the substrate, the MoO3 / CuO / Cu2O mixed nanoclusters 2 are deposited on the interdigital electrode on one side surface of the substrate, and the PTFE hydrophobic layer 4 covers the surface of the MoO3 / CuO / Cu2O mixed nanoclusters 2.
[0039] MoO3 / CuO / Cu2O mixed nanoclusters 2 are used as NH3 gas-sensitive materials and are deposited on a PET substrate 1 with interdigitated electrodes by a cluster beam deposition device 5. A PTEF hydrophobic layer 4 is deposited on the device surface by using an RF magnetron sputtering gun 6 to give the device the ability to resist humidity interference.
[0040] The MoO3 / CuO / Cu2O mixed nanoclusters 2 in the present invention are prepared by cluster beam deposition method, such as Figure 2As shown. In this process, a Haberland-type gas aggregation source (see DOI: 10.1116 / 1.577853) was used to synthesize nanoclusters. A dual-target magnetron sputtering gun was used to sputter Mo and Cu targets respectively (for details on the preparation of mixed nanoclusters using dual targets, please refer to: DOI: 10.1039 / D4CP00868E). In order to form metal oxide clusters, a small amount of oxygen (O2) was added to the buffer gas (argon, Ar) during sputtering. By controlling the amount of O2 introduced, the Cu clusters can be partially oxidized to prepare CuO / Cu2O mixed nanoclusters. On the other hand, introducing a sufficient amount of O2 can ensure that Mo is completely oxidized to MoO3. MoO3 / CuO / Cu2O mixed nanoclusters can be prepared by depositing CuO / Cu2O and MoO3 in sequence.
[0041] After the MoO3 / CuO / Cu2O mixed nanoclusters are deposited, the sample stage 7 is rotated 45 degrees to face the RF magnetron sputtering gun 6. The PTFE hydrophobic layer can be covered on the device surface by RF sputtering. Figure 2 shown.
[0042] In the embodiment of the present invention, the average molecular weight of PTFE is about 450,000-500,000, and the average molecular weight of PET is about 12,000-15,000.
[0043] Example 1: Preparation of MoO3 / CuO / Cu2O mixed nanocluster ammonia sensor and comparison of ammonia sensing performance with CuO / Cu2O mixed nanocluster, the specific steps are as follows:
[0044] (1) A 500 μm thick PET substrate was selected as the substrate and was ultrasonically cleaned in a mixture of hydrogen peroxide (30% by mass) and isopropanol in a volume ratio of 1:1 before use;
[0045] (2) preparing interdigital electrodes on a PET substrate by mask evaporation. For the specific preparation method, see Chinese Patent ZL201310257793.0. First, a layer of Ti with a thickness of 5-10 nm is deposited as an adhesion layer, and then a 50 nm thick Ag interdigital electrode is deposited by mask evaporation. The spacing between the interdigital electrodes is 150 μm.
[0046] (3) CuO / Cu2O nanoclusters were deposited on the PET substrate with the prepared interdigital electrodes by cluster beam deposition technology. Specifically, CuO / Cu2O nanoclusters were generated by magnetron plasma gas aggregation method. Metal Cu and Mo targets were placed on two sputtering guns of cluster beam deposition equipment, and the interdigital electrodes were placed in the deposition chamber of the cluster beam deposition system. The entire device was evacuated. Sputtering gas was first introduced into a sputtering gun loaded with Cu target, and buffer gas was introduced into the sputtering chamber of the cluster beam deposition system. High-purity Cu target (99.99%) was sputtered in a mixture of argon (Ar) and trace oxygen (O2) to control the partial oxidation of Cu and form CuO / Cu2O mixed nanoclusters. High-purity Ar (130 sccm) and O2 (0.02 sccm) were introduced into the aggregation chamber to adjust the oxidation state. The pressure in the sputtering chamber was maintained at 130 Pa, and the Cu target was sputtered at a DC sputtering power of 14 W. A quartz crystal microbalance (QCM) was used to monitor the deposition rate in real time, and a nanoparticle beam was formed by differential vacuum. The deposition was carried out at a rate of 1600s, and the deposition time was 1600s, and the generated CuO / Cu2O mixed nanoclusters were deposited on the interdigitated electrodes on the surface of the substrate, and the thickness of the CuO / Cu2O mixed nanocluster layer was about 150nm.
[0047] (4) After the deposition of CuO / Cu2O, MoO3 nanoclusters were deposited to form MoO3 / CuO / Cu2O multi-heterostructures. Mo was sputtered using another magnetron sputtering gun in a reaction atmosphere of Ar (130 sccm) and O2 (0.06 sccm) to produce fully oxidized MoO3. The sputtering power was set to 20 W and the deposition rate was maintained at The deposition time was 200 s, and fully oxidized MoO3 was produced and deposited on the CuO / Cu2O mixed nanoclusters, forming a multi-heterojunction structure of MoO3 / CuO / Cu2O mixed nanocluster layers.
[0048] (5) Through the above steps, two samples of CuO / Cu2O and MoO3 / CuO / Cu2O can be obtained. The two samples prepared above were tested for their ammonia response characteristics at room temperature. In the gas-sensitive performance test, the sensor was placed in a closed test chamber, and dry air was introduced as background gas at 5000sccm through a flowmeter. Another flowmeter was used to control the flow rate of ammonia, so that the sample was exposed to an ammonia environment with a concentration of about 5 to 1000ppm. In order to obtain the sensing signal, a digital source meter was used to apply a constant 1V DC bias to the sensor, and the current of the sensor was measured at the same time. The sensor response is defined as S=ΔI / I a × 100%, where ΔI = I a -I g ;I gand I a Represent the current values under ammonia and baseline (no ammonia) conditions respectively. From this, a response curve can be drawn ( Figure 3 ).
[0049] from Figure 3 It can be seen that the response sensitivity of the ammonia sensor based on MoO3 / CuO / Cu2O multi-heterostructure to ammonia is significantly higher than that of CuO / Cu2O, which indicates that the multi-heterostructure significantly improves the ammonia sensing performance.
[0050] Example 2: Prepare a PTFE-covered MoO3 / CuO / Cu2O multi-heterostructure sensor and compare its ammonia response performance under certain humidity conditions with that of a sensor not covered with PTFE.
[0051] (1) According to steps (1) to (4) of Example 1, two samples of CuO / Cu2O and MoO3 / CuO / Cu2O were prepared.
[0052] (2) PTFE coating was deposited on both CuO / Cu2O and MoO3 / CuO / Cu2O samples. The steps were as follows: the sample stage was rotated 45 degrees so that the sample was facing the RF magnetron sputtering gun. A layer of PTFE ( Figure 2 ). High-purity argon (Ar, 99.99%) was introduced into the deposition chamber at a flow rate of 2 sccm via a mass flow controller (Aitoly, MFC300) to maintain a stable pressure of 1 Pa. Sputtering was performed at a power of 85 W for 30 min to form a uniform PTFE coating on the MoO3 / CuO / Cu2O-based sensor;
[0053] (3) The sensor samples with and without PTFE deposited were subjected to ammonia sensing measurements according to step (5) in Example 1, using 5 ppm ammonia as the test gas and a bubbling method to generate a predetermined humidity condition (for details, see DOI: 10.1039 / D4CP00868E). The test results are as follows: Figure 4 shown.
[0054] from Figure 4 It can be seen that even under 95% relative humidity conditions, the sensor coated with the PTFE hydrophobic layer can still maintain a response value of about 10.5%, while the response value of the sensor without coating has dropped significantly. This result confirms the effectiveness of the TFE hydrophobic layer in enhancing the sensor's ability to resist humidity interference.
Claims
1. A flexible ammonia gas sensor based on multi-heterojunction nanoclusters, characterized in that The invention comprises a substrate, an interdigital electrode, a MoO3 / CuO / Cu2O mixed nanocluster layer and a hydrophobic layer. The interdigital electrode is arranged on one side surface of the substrate. The MoO3 / CuO / Cu2O mixed nanocluster layer is first deposited on the interdigital electrode on one side surface of the substrate. MoO3 enhances the adsorption of NH3 by forming a multi-heterojunction with CuO and Cu2O, and then the hydrophobic layer is coated on the surface.
2. A flexible ammonia gas sensor based on multi-heterojunction nanoclusters as claimed in claim 1, characterized in that The substrate is polyethylene terephthalate (PET) with a thickness of 50-1000 μm; the hydrophobic layer is made of polytetrafluoroethylene (PTFE) with a thickness of 500-5000 nm.
3. A flexible ammonia gas sensor based on multi-heterojunction nanoclusters as claimed in claim 1, characterized in that The materials of the interdigital electrodes are titanium and silver, and the spacing between the interdigital electrodes is 50~400 μm.
4. The method for preparing a flexible ammonia gas sensor based on multi-heterojunction nanoclusters according to claim 1, characterized in that The following steps are involved: 1) preparing interdigital electrodes on a substrate by mask evaporation to obtain a substrate with interdigital electrodes; 2) CuO / Cu2O nanoclusters were deposited on a substrate with interdigital electrodes using cluster beam deposition technology. Metal Cu and Mo targets were placed on two sputtering guns of the cluster beam deposition equipment. The interdigital electrodes were placed in the deposition chamber of the cluster beam deposition system, and the entire device was evacuated. First, a sputtering gas is introduced into a sputtering gun loaded with a Cu target, and a buffer gas is introduced into the sputtering chamber of the cluster beam deposition system. The buffer gas is mainly Ar and a small amount of O2 is introduced into it. By adjusting the oxygen content, incomplete oxidation of Cu is achieved, thereby generating a heterogeneous structure of CuO / Cu2O mixed nanoclusters deposited on the interdigital electrodes on the surface of the substrate; 3) After step 2), the O2 content in the buffer gas is increased, and another sputtering gun loaded with a Mo target sputters Mo in a reaction atmosphere containing a relatively high O2 content, thereby generating fully oxidized MoO3 and depositing it on the CuO / Cu2O mixed nanoclusters, thereby forming a multi-heterojunction structure of the MoO3 / CuO / Cu2O mixed nanocluster layer; 4) A hydrophobic layer was coated on the surface of the MoO3 / CuO / Cu2O mixed nanocluster layer of the sensor by radio frequency magnetron sputtering to improve the moisture resistance.
5. The method for preparing a flexible ammonia gas sensor based on multi-heterojunction nanoclusters according to claim 4, characterized in that In step 2), the gas pressure in the sputtering chamber is maintained at 100-150 Pa, the sputtering power of the Cu target is set to 10-15 W, the O2 content in the buffer gas is 0.01-0.02%, the deposition rate is 0.1-0.3 Å / s, and the deposition time is 100-2000 s, preferably 1200-2000 s.
6. The method for preparing a flexible ammonia gas sensor based on multi-heterojunction nanoclusters according to claim 4, characterized in that In step 3), the pressure in the sputtering chamber is maintained at 100-150 Pa, the sputtering power of the Mo target is set to 18-25 W, the O2 content in the buffer gas is 0.04-0.1%, the deposition rate is 0.05-0.2 Å / s, and the deposition time is 60-300 s, preferably 100-300 s. When depositing MoO3, the oxygen flow rate is adjusted to ensure that the Mo element is completely oxidized to Mo 6+ , thereby forming MoO3 with high adsorption activity and stability, and finally realizing MoO3 / CuO / Cu2O multi-heterogeneous structure.
7. The method for preparing a flexible ammonia gas sensor based on multi-heterojunction nanoclusters according to claim 4, characterized in that Step 2) The thickness of the prepared CuO / Cu2O mixed nanocluster layer is controlled to be 10~200nm.
8. The method for preparing a flexible ammonia gas sensor based on multi-heterojunction nanoclusters according to claim 4, characterized in that In the MoO3 / CuO / Cu2O mixed nanocluster layer prepared in step 3), the content of MoO3 is 3-7%.
9. Application of the flexible ammonia gas sensor based on multi-heterojunction nanoclusters as claimed in claim 1 in detecting ammonia concentration.
10. The use according to claim 9, characterized in that The sensor can operate in a temperature range of −10 to 60°C and maintain sensitivity and stability in an environment with a relative humidity of more than 90%.
Citation Information
Patent Citations
Palladium nano particle dot matrix hydrogen sensor with controllable sensing parameters
CN103336036A